(untitled) (International journal of artificial intelligence, 2026)
Anaphylactic shock represents one of the most critical emergency conditions requiring immediate medical intervention and competent nursing care. This article examines the theoretical foundations and practical aspects of nursing interventions in anaphylactic shock management through comprehensive literature analysis. The findings underscore the necessity of continuous professional development for nursing staff and implementation of standardized care protocols in healthcare institutions.